Customised birthweight standards accurately predict perinatal morbidity. Issue 4 (24th January 2007) - Figueras, Francesc; Figueras, Josep; Meler, Eva; Eixarch, Elisenda; Coll, Oriol; Gratacos, Eduard; Gardosi, Jason; Carbonell, Xavier
Abstract : Objective: Fetal growth restriction is associated with adverse perinatal outcome but is often not recognised antenatally, and low birthweight centiles based on population norms are used as a proxy instead. This study compared the association between neonatal morbidity and fetal growth status at birth as determined by customised birthweight centiles and currently used centiles based on population standards. Design: Retrospective cohort study. Setting: Referral hospital, Barcelona, Spain. Patients: A cohort of 13 661 non-malformed singleton deliveries. Interventions: Both population-based and customised standards for birth weight were applied to the study cohort. Customised weight centiles were calculated by adjusting for maternal height, booking weight, parity, ethnic origin, gestational age at delivery and fetal sex. Main outcome measures: Newborn morbidity and perinatal death. Results: The association between smallness for gestational age (SGA) and perinatal morbidity was stronger when birthweight limits were customised, and resulted in an additional 4.1% (n = 565) neonates being classified as SGA. Compared with non-SGA neonates, this newly identified group had an increased risk of perinatal mortality (OR 3.2; 95% CI 1.6 to 6.2), neurological morbidity (OR 3.2; 95% CI 1.7 to 6.1) and non-neurological morbidity (OR 8; 95% CI 4.8 to 13.6). Conclusion: Customised standards improve the prediction of adverse neonatal outcome. The association between SGA and adverse outcome is independent of the gestational age at delivery.